95.8k views
3 votes
If f(x) = x^2 + 2x - 4 and g(x) = - 4x +1, what is (g-f)(x)?

User Mantu
by
5.0k points

1 Answer

3 votes

Answer: -x^2 - 6x + 5

===================================================

Work Shown:

(g - f)(x) = g(x) - f(x)

(g - f)(x) = (-4x+1) - (x^2+2x-4)

(g - f)(x) = -4x+1 - x^2-2x+4

(g - f)(x) = -x^2+(-4x-2x)+(1+4)

(g - f)(x) = -x^2 - 6x + 5

User Mcatis
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.